Geochemistry of Volcanic Rocks (Yüksekova Complex) around Uslu (S Elazığ) - Ural, Melek; Cihan, Ayşe (My University, 2021)
The study area is located approximately 50 km south of Elazığ city within the Southeastern Anatolian Orogenic Belt (SEAOB). In the area, the volcanic rocks of the Upper Cretaceous Yüksekova Complex were tectonically overlain by mantle cumulates consisting of harzburgite, dunite and Iherzolites belonging to the Late Cretaceous aged Kömürhan Ophiolites. The Yüksekova Complex unconformably overlies the Permo-Triassic Pütürge Metamorphics and in places has tectonic contact. The volcanicrocks around Uslu (S Elazığ) are massive lavas and have basaltic composition. Mineralogically and texturally recognizable lavas are rich in plagioclase and opaque oxide minerals. Secondarily, calcite mineral is dominant. Amygdaloidal textures are common. According to the trace element distributions of the rock samples normalized to N-OOSB; LIL elements are enriched according to HFS elements. LREEs, on the other hand, show a richer distribution than HREEs. As a result; the geochemical data together with previous studies point to the rifting of the oceanic arc, which reveals that the volcanic facies outcropping around Uslu have no genetic relationship with the Maden Complex.
Keywords: Uslu (S Elazığ); Yüksekova Karmaşığı; Massive lava